Microwave-assisted synthesis and bioevaluation of new sulfonamides - Halise Inci Gul; Cem Yamali; Fatma Yesilyurt; Hiroshi Sakagami; Kaan Kucukoglu; Ilhami Gulcin; Mustafa Gul; Claudiu T. Supuran (Taylor & Francis Group, 2017)
In this study, 4-[5-(4-hydroxyphenyl)-3-aryl-4,5-dihydro-1H-pyrazol-1-yl]benzenesulfonamide derivatives (8-14) were synthesized for the first time by microwave irradiation and their chemical structures were confirmed by 1H NMR, 13C NMR and HRMS. Cytotoxic activities and inhibitory effects on carbonic anhydrase I and II isoenzymes of the compounds were investigated. The compounds 9 (PSE = 4.2), 12 (PSE = 4.1) and 13 (PSE = 3.9) with the highest potency selectivity expression (PSE) values in cytotoxicity experiments and the compounds 13 (Ki = 3.73 ± 0.91 nM toward hCA I) and 14 (Ki = 3.85 ± 0.57 nM toward hCA II) with the lowest Ki values in CA inhibition studies can be considered as leader compounds for further studies.